Strategy for Preventing Potential Conflicts in the Establishment of Religious Minority Houses of Worship in the City of Semarang - Suneki, Sri; Yunus, Mahmud; ., Haryono (KnE Social Sciences, 2024)
Semarang City is a city that has social, religious, and cultural diversity. There is currently potential for conflict in several areas of Semarang City due to the rejection of the establishment of religious minority places of worship. The purpose of this research is to reveal the potential causes of conflicts over the construction of houses of worship of minority religions and to find appropriate strategies to prevent conflicts from occurring due to the construction of houses of worship of the majority religion. This qualitative research adopted a case study approach with data collection techniques of observation, documentation, and in-depth interviews with key informants and supporting informants. The results of this study indicate that in the Tlogosari and Sendangmulyo areas there is the potential for conflicts to occur against the background of the construction of a church house of worship, the root cause of this potential conflict is due to the refusal of permits. The conflict prevention strategy is to provide social education to the community regarding pluralism education with a social approach that is carried out with synergy between the government and the community. The implications of this research can be used as a reference by the Semarang City Government in preventing conflicts due to the establishment of religious minority places of worship. Keywords: conflict prevention; conflict potential; social conflict; religious conflict